2021
DOI: 10.21608/epsj.2021.159922
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of in-Ovo Injection of Bee Venom on Hatchability and Some Immunological Parameters of Alexandria Chicks’ Strain at Hatch

Abstract: Researchers are trying to boost the immune system of poultry birds through the use of natural immune-stimulants including bee venom. There is a scarcity in literature about the use of bee venom for in ovo injection studies. The aim of this study is to investigate the effect of in ovo injection of two levels of freeze-dried bee venom (BV) (10 and 20 µg/egg) into eggs of Alexandria breeder hens at 18-day of incubation on the hatchability percentage, hatching weight per egg weight, and immune response of the youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the same line, Rabie et al (2018) noted that feeding Cobb 500 chicks propolis (200 mg/kg diet) or adding BV (1 or 2 mg/L) to their drinking water led to significantly larger relative spleen and bursa weights compared to the control group. Similarly, Hassan et al (2021) found that Alexandria chicks injected in‐Ovo with 20 μg BV/egg had higher relative spleen and bursa weights (0.09% and 0.15% respectively) than the control group. In contrast, Ibrahim el‐Malky et al (2021) observed no significant differences in the relative weights of the gizzard, liver, heart, spleen or intestine of Ross 308 broiler chicks fed with a mixture of Melittin in drinking water and Thepax in formulated diets at the end of the experimental period (35 days of age).…”
Section: Discussionmentioning
confidence: 83%
“…In the same line, Rabie et al (2018) noted that feeding Cobb 500 chicks propolis (200 mg/kg diet) or adding BV (1 or 2 mg/L) to their drinking water led to significantly larger relative spleen and bursa weights compared to the control group. Similarly, Hassan et al (2021) found that Alexandria chicks injected in‐Ovo with 20 μg BV/egg had higher relative spleen and bursa weights (0.09% and 0.15% respectively) than the control group. In contrast, Ibrahim el‐Malky et al (2021) observed no significant differences in the relative weights of the gizzard, liver, heart, spleen or intestine of Ross 308 broiler chicks fed with a mixture of Melittin in drinking water and Thepax in formulated diets at the end of the experimental period (35 days of age).…”
Section: Discussionmentioning
confidence: 83%
“…According to numerous studies, the nutrients in the egg are insufficient to enable maximum growth (Zielinska et al, 2011), As a result, researchers are looking into in-ovo feeding as a way to provide more nutrients. In-ovo injection of different nutrients provides directly to the growing fetus for development (Hassan et al, 2018;Jha et al, 2019), and helps to overcome any constraint of inadequate egg nutrition (Selim et al, 2012). The present results are in acceptance of the results of Abd El-Fatah et al (2018) showed that Arbor Acres broiler chick hatch body weight of in-ovo injection with SeNPs (0, 10, and 20 μg/ egg) at day 16 of incubation has significant differences (40.63, 39.56, and 40.00 g, respectively).…”
Section: Results and Discussion Chick And Hatchability Traitsmentioning
confidence: 99%
“…Then, using 21 needle-gauge at 18 days of incubation, all eggs from the 2 nd to the 5 th groups were injected from the top of the egg with in-ovo injection solutions (0.5 ml/ egg) into the amniotic fluid. The site of injection was sanitized with ethanol 70 % and sealed by using the wax gun after injection as described by Hassan et al (2018). Throughout the incubation period, all eggs were incubated according to the common routine procedures.…”
Section: In-ovo Injection Proceduresmentioning
confidence: 99%
“…According to El-Speiy et al [48], using bee venom up to 2 mg/kg body weight/day can improve immunological and antioxidative activities while decreasing harmful microorganisms in the hindgut of weaning rabbits. Bee venom has a positive influence on some biochemical parameters such as total protein, albumin, and globulin concentration in animal blood, as well as stimulating liver enzyme activity (aspartate and alanine aminotransferase) [99]. Furthermore, melittin (the active extract of bee venom) regulates cell membrane modifications by influencing the interactions of lipoproteins that affect the development of these membranes [100].…”
Section: Bee Venommentioning
confidence: 99%